THE EFFECTIVENESS OF COMMUNICATION IN ONLINE LEARNING: A STUDY ON UIN ANTASARI STUDENTS DURING THE COVID-19 PANDEMIC - Surya Eka Priyatna; Ilham . (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
This study provides qualitative analysis results in obtained from research at UIN Antasari Banjarmasin. In particular, this study aims to provide an overview of the situation and solutions for improving the results of online learning studies. Five hundred twenty-six students of class 2018 semester six and class 2019 semester 4 for the 2020/2021 academic year were involved as informants and respondents in 5 research stages, namely Focus Group Discussion, Case Study Analysis, Data Triangulation, SWOT Analysis, Strategic Management Determination. The results show that 1) the management and online learning methods are still not optimal, and the communication relationship between lecturers and students causes difficulties in adapting and understanding the material. 2) The determining factors for the success of online studies are good communication, appropriate management, lecture methods, regulatory policies, and the provision of operational facilities for online learning from institutions. 3) Based on the SWOT quadrant analysis, the state of student study is in quadrant I with coordinates 0.26; 0.40, and an aggressive growth policy can be applied to develop online learning.